Correlations between cardiac troponin I and nonsustained ventricular tachycardia in hypertrophic obstructive cardiomyopathy. Issue 10 (18th August 2020) - Liu, Limin; Liu, Shangyu; Shen, Lishui; Tu, Bin; Hu, Zhicheng; Hu, Feng; Zheng, Lihui; Ding, Ligang; Fan, Xiaohan; Yao, Yan
Abstract: Background: Nonsustained ventricular tachycardia (NSVT) is an independent risk factor for sudden cardiac death (SCD) in patients with hypertrophic obstructive cardiomyopathy (HOCM). However, data concerning the correlations of cardiac biomarkers and NSVT in HOCM are rather limited. Hypothesis: Our study aimed to investigate the associations between the occurrence of NSVT and circulating biomarkers representing myocardial injury (cardiac troponin I, cTnI), cardiac function (N‐terminal pro‐brain natriuretic peptide, NT‐pro BNP), and inflammation (high‐sensitivity C‐reactive protein) in a large Chinese HOCM cohort. Methods: A total of 755 consecutive HOCM patients were recruited. Systematic cardiac evaluations and circulating biomarkers were examined routinely in all subjects under the clinically stable status. According to the results of 24‐hour Holter monitoring, patients were divided into the NSVT group (n = 138) and the nonventricular tachycardia (non‐VT) group (n = 617). Results: Compared with the non‐VT group, circulating levels of both cTnI and NT‐pro BNP elevated significantly in patients with positive NSVT episodes ( P  < .001). Multivariable analyses demonstrated that cTnI was independently associated with the presence of NSVT (OR = 1.675, 95% CI: 1.406‐1.994, P  < .001). Concentrations of cTnI increased progressively not only with the aggravation of ventricular arrhythmic events ( P  < .001), but also with the growing risk of SCD in HOCM patients ( P  < .001). Serum cTnI ≥ 0.0265 ng/mL indicated predictive value for the occurrence of NSVT in the HOCM cohort (area under the curve = 0.707, 95% CI: 0.660‐0.754, P  < .001). Conclusions: Elevated cTnI was an independent determinant of NSVT, and it seemed to be valuable for assessing the clinical status of ventricular arrhythmias and the risk of SCD in patients with HOCM.